A Quest for Green Consumerism in Sri Lankan Context: An Application of Comprehensive Model - S, Achchuthan; T, Velnampy (Asian Journal of Empirical Research, 2016)
Study is directed towards green consumerism in the Sri Lankan context. Topic is new and considered as an emerging one in the marketing paradigm. Meanwhile, this study focuses on green consumerism among young consumers in Sri Lankan stand point. Proposed model in this study was designed as the extension of Theory of Planned Behavior (TPB). Exploratory Factor Analysis, Confirmatory Factor Analysis and Structural Equation Modeling were utilized as advanced statistical techniques to approach the research questions in this study frame. In this context, results revealed that, green purchase intention was significantly influenced by environment attitude, perceived consumer effectiveness and health consciousness. In contrast, green purchase intention was not significantly influenced by media influence, environmental concern, social influence and perceived government initiatives. In addition, Young consumers in Sri Lankan perspective have favorable mindset towards green purchase. In practice, marketers of the green products might focus on marketing communication to enhance the environmental attitude, effectiveness in green consumerism and health consciousness among young consumers, which might tap the consumers’ mindset to prefer the green products.